In-situ construction method of living carbonaceous semiconductor material and application of living carbonaceous semiconductor material in photocatalytic degradation of pollutants
By using bacterial enzyme catalytic system to construct live carbonaceous semiconductor materials in situ in contaminated water treatment, the problems of low efficiency and high cost of pollutant removal in the prior art are solved, and efficient, environmentally friendly and sustainable pollutant degradation effects are achieved. .
Patent Information
- Application Number
- CN202510036517.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-14
AI Technical Summary
The existing polluted water treatment technology has the problems of high cost of chemical methods, high energy consumption of physical methods, and low biological methods for treatment efficiency, making it difficult to achieve efficient, sustainable and environmentally friendly removal of pollutants.
By using a bacterial enzyme catalytic system to construct live carbonaceous semiconductor materials with sulfide semiconductors as photosensitizers, carbon materials as bridges, and microorganisms as catalytic sites in situ, photocatalytic degradation of pollutants is achieved.
This method can efficiently remove pollutants in wastewater, including nitrates, antibiotics and organic dyes under mild conditions, with high degradation efficiency, low cost and environmentally friendly.
Smart Images

Figure CN119432928A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sewage and wastewater treatment, and specifically relates to an in-situ construction method of a living carbonaceous semiconductor material and an application thereof in photocatalytic degradation of pollutants. Background Art
[0002] The removal of pollutants such as nitrates, sulfonamide antibiotics or methyl dyes in wastewater usually adopts chemical methods including precipitation, adsorption and ion exchange, physical methods including evaporation, and biological methods including microbial and phytoremediation. Among them, chemical methods require the addition of additional high-cost chemical reagents, produce a large amount of pollutants and are prone to secondary pollution; distillation methods have high energy consumption and high operating costs; phytoremediation cycles are long and are greatly affected by the environment. Compared with other methods, microbial removal has the advantages of low cost and environmental friendliness, but the conventional microbial treatment efficiency is not as good as the chemical method.
[0003] Some microorganisms can synthesize semiconductors with photocatalytic activity under mild conditions, and can remove pollutants efficiently under the premise of being environmentally friendly. Considering the photosensitivity of semiconductor materials, the large specific surface area of carbon materials and the catalytic function of microbial enzymes, the microorganisms of the present invention synthesize photosensitizer sulfide semiconductors in situ, and the carbon materials are the link between semiconductor materials and organisms, thereby constructing living carbonaceous semiconductor materials to achieve sustainable, green and efficient removal of pollutants in wastewater. Summary of the invention
[0004] In view of this, the present invention provides an in-situ construction method of a living carbonaceous semiconductor material and its application in photocatalytic degradation of pollutants. The present invention makes full use of the bacterial enzyme catalytic system, recovers heavy metal ions in situ, and constructs a living carbonaceous semiconductor material with a sulfide semiconductor as a photosensitizer, a carbon material as a bridge, and microorganisms as catalytic sites. The living carbonaceous semiconductor material has the ability to generate electrons under light to promote the degradation of pollutants, thereby achieving efficient degradation of pollutants.
[0005] The in-situ construction method of the living carbonaceous semiconductor material of the present invention comprises the following steps:
[0006] Step 1: Cultivate the dissimilatory metal-reducing bacteria in LB medium until the late logarithmic growth stage;
[0007] Step 2: The dissimilatory metal-reducing bacteria cultured to the late logarithmic growth stage in step 1 are resuspended in a culture medium containing thiosulfate for anaerobically cultured. After a period of reaction, heavy metal ions and carbon materials are added to the culture system to convert all heavy metal ions into sulfide semiconductors, thereby obtaining living carbonaceous semiconductor materials.
[0008] In step 1, the dissimilatory metal-reducing bacteria stored at -80°C were streaked on a plate, cultured aerobically for 48 h, and then single colonies were selected in LB liquid culture medium. After another 12 h of aerobic culture, they were transferred to fresh LB liquid culture medium at a ratio of 1:10 and continued to be cultured aerobically for 12 h.
[0009] The dissimilatory metal-reducing bacteria is the wild-type WT strain of S. oneidensis MR-1.
[0010] In step 2, the culture medium containing thiosulfate is based on LB liquid culture medium, to which thiosulfate is added, and the concentration of thiosulfate is between 0.1-5 mM.
[0011] In step 2, the concentration of the heavy metal ions in the culture system is between 0.1-5 mM, and the type of the heavy metal ions can be one or more of Cd(II), Hg(II), Cu(II), Pb(II), etc.
[0012] In step 2, the concentration of the carbon material in the culture system is between 10-500 mg / L, and the carbon material includes one or more of graphene oxide and activated carbon.
[0013] Furthermore, in step 2, the anaerobic culture time of thiosulfate is 6-12 h; the thiosulfate is sodium thiosulfate. The culture time after adding heavy metals and carbon materials is 6-12 h.
[0014] The concentrations of sodium thiosulfate, heavy metals and carbon materials affect the performance, especially the bacterial activity and enzyme function. After optimization, the present invention uses 0.3 mM sodium thiosulfate, 0.3 mM heavy metals and 50 mg / L carbon materials.
[0015] In step 2, the anaerobic culture is achieved by aeration with nitrogen for 30 min.
[0016] The invention discloses an application of the living carbonaceous semiconductor material in photocatalytic degradation of pollutants.
[0017] The pollutants include one or more of nitrates, antibiotics, and organic dyes.
[0018] The nitrate includes one or more of lithium, sodium and potassium nitrates; the antibiotic is a sulfonamide antibiotic, such as sulfamethoxazole; and the organic dye is a methyl dye, such as methyl green, methyl orange, methyl red, methyl blue and the like.
[0019] In the present invention, a xenon lamp is used as the light source, and the light intensity is 20mW / cm 2 .
[0020] Specifically, the living carbonaceous semiconductor material is transferred into a liquid inorganic salt culture medium containing pollutants, and then photocatalytically degraded after being fully aerated in an argon atmosphere for 30 minutes. The concentration of the added living carbonaceous semiconductor material is consistent with the concentration in the previous synthesis, that is, 50 mg / L. The nitrate concentration is 0.1-10 mM, the antibiotic concentration is 1-200 mg / L, and the organic dye concentration is 1-500 mg / L.
[0021] The concentration of pollutants will also affect bacterial activity and enzyme function. In the implementation process, the present invention uses 1 mM nitrate, 30 mg / L sulfamethoxazole or 100 mg / L methyl green.
[0022] The components of the liquid inorganic salt culture medium are: NaCl 0.4-0.5 g / L, (NH4)2SO4 0.2-0.3 g / L, K2HPO4·3H2O 2.5-3.5 g / L, KH2PO4 2-3 g / L, Na2HPO4·12H2O 8.5-9.5 g / L, NaH2PO4·2H2O 2-3 g / L, MgSO4·7H2O 0.02-0.03 g / L, and sodium lactate 15-25 mM.
[0023] In the following examples, the composition of the liquid inorganic salt culture medium is shown in Table 1 below.
[0024]
[0025] During the experiment of the present invention, the following control groups were set up for comparison: a living carbonaceous semiconductor material dark group and a pure material control group that inhibits the activity of microorganisms. The anaerobic culture time in both light and dark was 2 h.
[0026] Although the photocatalytic degradation of pollutants by assembling microorganisms and semiconductor materials has been reported, the insufficient contact between the microorganisms and the semiconductor materials results in incomplete and discontinuous electron transfer, resulting in low electron utilization and low pollutant degradation efficiency. At the same time, the reported sulfide / carbon material assembly is a direct mixture of chemically synthesized materials and microorganisms. The photocatalytic performance of the photosensitizer synthesized in this way is lower than that of the photosensitizer synthesized in situ by biological methods in the present invention.
[0027] In this study, the microorganisms and materials can be fully contacted by regulating the reaction time. When Shewanella reduces sodium thiosulfate for 6-12 hours, tightly connected CdSNPs can be formed outside the bacterial cell; when it is more than 15 hours, the CdS NPs formed are easily dispersed in the solution, which is reflected in the fact that after adding heavy metal ions Cd(II), the solution slowly turns yellow within 2-5 minutes and the solution turns yellow instantly. Then, graphene oxide GO is added and fully reacted for 6-12 hours, so that Shewanella fully reduces GO to reduced graphene oxide RGO. Its good interface construction comes from the fact that both Shewanella and GO are hydrophilic (contactable), and both have functional groups such as -OH and -NH (amino and hydroxyl groups can undergo multiple reactions).
[0028] Therefore, the present invention in situ biologically self-assembles a living carbonaceous semiconductor material, utilizes the biological enzyme catalytic ability of S. oneidensisMR-1, in situ constructs a living material with interface contact between microorganisms, sulfide semiconductors and carbon materials, and uses it for photocatalytic degradation of pollutants.
[0029] Compared with the reported pollutant degradation methods, the present invention has the following advantages:
[0030] The present invention can recover heavy metal ions while synthesizing sulfide semiconductor materials in situ in an environmentally friendly and mild microbial enzyme catalytic manner. It does not involve toxic solvents and is simple to operate and pollution-free. The biosynthesized sulfide photosensitizer of the present invention is completely different from the chemically synthesized photosensitizer and has better performance. At the same time, due to the catalytic ability of microbial enzymes, carbon materials can be reduced in situ, thereby improving their conductivity. The living carbonaceous semiconductor material constructed in situ of the present invention has the ability to degrade a variety of pollutants, including nitrates, sulfonamide antibiotics, and methyl dyes, and has high degradation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 is the OD of the living carbonaceous semiconductor material CdS / RGO / SW in Example 1 after the reaction under different precursor concentration conditions and the transfer culture 600 Value (reflecting microbial activity).
[0032] Figure 2 (A) is the contact angle result of graphene oxide GO and Shewanella in Example 1, (B) and (C) are the infrared spectrum results of graphene oxide GO and Shewanella in Example 1, respectively.
[0033] Figure 3 The scanning electron microscope (SEM) of the living carbonaceous semiconductor material CdS / RGO / SW in Example 1 (A) and the statistical results of the biosynthesized CdS particle size (B).
[0034] Figure 4The scanning electron microscope (SEM) of the active carbonaceous semiconductor material CdS / RGO / SW in Example 1 (A) and the corresponding mapping results (B).
[0035] Figure 5 (A) and (B) are the Raman spectra (Raman) and X-ray diffraction (XRD) results of various materials purified in Example 1, respectively; Figure 5 (CE) and (F) are the X-ray photoelectron spectroscopy (XPS) results of CdS / RGO and RGO in Example 1, respectively; Figure 5 (G) is the photocurrent response it curve results of CdS / RGO and CdS in Example 1.
[0036] Figure 6 (A) is the OD of the living carbonaceous semiconductor material CdS / RGO / SW in Example 2 after 2 hours of reaction under the pollutant concentration conditions. 600 value (reflecting microbial activity); Figure 6 (BD) are the degradation rate results of the living carbonaceous semiconductor material CdS / RGO / SW and the control material CdS / RGO in Example 2 for pollutants of different concentrations including nitrate (B), methyl green (C) and sulfamethoxazole (D) under 2 h of light or darkness.
[0037] Figure 7 The SEM (A) of the chemically synthesized material CdS / RGO and the statistical results of the CdS particle size (B) in Example 3 are shown. Figure 7 (C)Figure shows the XRD results of CdS / RGO.
[0038] Figure 8 The degradation rates of nitrate (A), methyl green (B), and sulfamethoxazole (C) by the living carbonaceous semiconductor material CdS / RGO / SW and the control material CdS / RGO in Example 3 under 2 h of light or darkness. DETAILED DESCRIPTION
[0039] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below. The following content is only an example and explanation of the concept of the present invention. The technicians in the relevant technical field make various modifications or supplements to the specific implementation cases described or replace them with similar methods. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0040] The present invention utilizes the catalytic ability of microbial enzymes to construct in situ a living carbonaceous semiconductor material composed of S. oneidensis MR-1-sulfide semiconductor and carbon material, which can achieve efficient degradation of pollutants under light. Compared with most existing chemical methods for degrading pollutants, the present invention has mild reaction conditions, is environmentally friendly, has low cost, and has high efficiency in degrading pollutants. At the same time, CdS / RGO was synthesized by chemical synthesis, and it was found that the CdS / RGO synthesized by the chemical method and the CdS / RGO synthesized by the biological method of the present invention have great differences in morphology, particle size, crystal form, etc., and the degradation effect of pollutants after interaction with microorganisms is lower than the degradation effect of in situ synthesis by the biological method.
[0041] The present invention uses a commercially available wild-type strain (WT) of dissimilatory metal-reducing bacteria S. oneidensis MR-1, and its commercial serial number information is as follows: Shewanella oneidensis ATCC 700550, MR-1; Taxonomy ID: 211586).
[0042] The following further describes the in-situ construction method of a living carbonaceous semiconductor material provided by the present invention and its application in photocatalytic degradation of pollutants.
[0043] Example 1: In situ biological construction of living carbonaceous semiconductor material CdS / RGO / SW by Shewanella oneidensis MR-1
[0044] (1) Biological construction of living carbonaceous semiconductor material CdS / RGO / SW: The wild-type strain of S. oneidensis MR-1 was cultured in LB medium until the late logarithmic growth period, and then the bacteria were collected and washed at 6000 rpm and washed with phosphate buffered saline (PBS) at least 3 times. 600 = 0.2, resuspended in LB medium containing a certain concentration of sodium thiosulfate, and then added with corresponding concentrations of Cd(II)-EDTA and graphene oxide GO after anaerobic culture for 6 hours, and continued anaerobic culture for 12 hours to obtain the living carbonaceous semiconductor material CdS / RGO / SW. The concentrations of the added precursors are shown in Table 2.
[0045]
[0046] (2) Optimization of conditions for the construction of living carbonaceous semiconductor materials CdS / RGO / SW: The different precursor concentrations in (1) were transferred and cultured at a ratio of 1:100. The culture conditions were 200rpm, 30℃, and 12h. The OD600 absorbance was measured to determine the bacterial activity. The goal was to select the largest possible concentration to improve the catalytic efficiency without causing a significant impact on the bacterial activity. Figure 1 It is known that the optimized experimental conditions are in situ synthesis of 0.3 mM CdS and 50 mg / L GO.
[0047] (3) Recovery of living carbonaceous semiconductor material CdS / RGO / SW: The CdS / RGO / SW material synthesized after the optimized conditions in (2) was collected by centrifugation at 6000 rpm and washed with water three times. Finally, the solid obtained by centrifugation was freeze-dried by vacuum freeze drying and ground into powder using an agate mortar for subsequent XRD, XPS and other characterizations.
[0048] (4) Conduct relevant index tests on the feasibility of this embodiment: freeze-dry the cultured Shewanella and grind it into powder, then press it or graphene oxide GO into tablets for contact angle and infrared spectrum tests. Figure 2 (A) It can be seen that both graphene oxide GO and Shewanella have good hydrophilicity, indicating that the two may have contact with each other; Figure 2 (BC) shows that both contain hydroxyl, amino or amide functional groups that can react with each other in various ways (1399, 3425 cm -1 Hydroxyl groups, 1242, 3220, 3300 cm -1 amino group, 1651 cm -1 The same hydrophilicity and interactive functional groups are the basis for the two to form a good contact and interaction interface.
[0049] (5) The performance index of the living carbonaceous semiconductor material constructed in situ in this embodiment is tested.
[0050] Scanning electron microscope (SEM) sample preparation: The living carbonaceous semiconductor material optimized in (2) was washed three times with PB buffer (pH = 7.2) by centrifugation, fixed with 2.5% glutaraldehyde, and kept at 4°C overnight. The next day, it was washed three times with PB buffer (PH = 7.2) by centrifugation, and then dehydrated with different concentrations of ethanol gradient (30%, 50%, 70%, 80%, 90%, 93%, 95%, 97%, 100%), and the living carbonaceous semiconductor material was soaked for 20 minutes at each concentration. Finally, the dehydrated living carbonaceous semiconductor material was dropped on a silicon wafer and observed with SEM. The centrifugation conditions involved in SEM sample preparation are 6000rpm, 5min, 4°C. Figure 3 (A) It can be seen that the CdS NPs synthesized in situ by microorganisms are distributed outside the cells in large quantities, and exist in two forms: riveted to the cell outer membrane and adhered to graphene. The microorganisms also adhere well to graphene. Figure 3 (B) Statistical analysis of particle size showed that the particle size of biologically synthesized CdS NPs was approximately 28.14 nm. Figure 4 (AB) shows the scanning electron microscopy and corresponding energy spectrum results of the synthesized nanomaterials, which shows that the nanomaterials are composed of Cd and S elements, while the C and O elements reflect the microbial components well.
[0051] Raman spectroscopy (Raman) sample preparation: The living material obtained in (2) was purified, freeze-dried, ground into powder, resuspended in water, and then dropped onto a glass slide wrapped in tin foil. Under the conditions of 532 nm laser excitation, 50x objective, 10 mW laser power, 3 s exposure time, and 2 accumulations, the Raman spectrum of the mixed sample on the tin foil plate was obtained. The Raman shift range was 100 ~ 3000 cm -1 Among them, the purification process is: first resuspend and wash with 2% sodium dodecyl sulfate (SDS, 55℃, water bath for 1 h) and proteinase K (100 ug / mL, 55℃, 0.5 h), and then ultrasonically disrupt (200 W, ultrasonic for 4 s, interval of 6 s, repeated 90 times) to lyse the bacteria and obtain the purified substance. Between different operations, the sample was washed with ultrapure water at least three times. I of graphene D / I G The value can reflect its redox state, Figure 5 (A) shows that graphene oxide was successfully reduced after microbial treatment. It is reported that RGO has a stronger conductivity than GO. The present invention relates to a relatively mild microbial method to successfully synthesize CdS NPs materials and RGO, and the nanomaterials, RGO and microorganisms are in close contact.
[0052] X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) sample preparation: The powdered solid sample in (3) was characterized. Figure 5 (B) is the XRD result, corresponding to the CdS card (PDF#10-0454). Figure 5 (CF) is the XPS result, which shows that the proportion of oxygen-containing functional groups in RGO after microbial treatment is lower than that of the original GO. The above once again proves the successful synthesis of CdS and the successful reduction of GO.
[0053] Test of photocatalytic ability of living carbonaceous semiconductor materials: The powdered solid sample in (3) was characterized by photocurrent it through a three-electrode system. The light source was a 300 W xenon lamp, and a 420 nm filter was used under a standard three-electrode system with a potential of -0.3 V. Figure 5 (G) shows that the constructed living carbonaceous semiconductor material produces a sudden current under light and the current decreases after the light source is removed, indicating that the living material has photoelectric response ability and has the potential to photocatalytically degrade pollutants.
[0054] Example 2: Photocatalytic degradation of various pollutants by living carbonaceous semiconductor material CdS / RGO / SW
[0055] (1) Optimization of pollutant degradation conditions of living carbonaceous semiconductor materials CdS / RGO / SW: The living carbonaceous semiconductor materials were resuspended in an inorganic salt culture medium containing pollutants, where the CdS concentration was 0.3 mM and the RGO concentration was 50 mg / L. The composition of the liquid inorganic salt culture medium was shown in Table 1, and the pollutant addition concentration was shown in Table 3.
[0056]
[0057] (2) Photocatalytic degradation of various pollutants by living carbonaceous semiconductor material CdS / RGO / SW: The living carbonaceous semiconductor material CdS / RGO / SW optimized in Example 1 and the control material CdS / RGO were subjected to the photocatalytic degradation experiment under different pollutant concentration conditions in Example 2 (1). A xenon lamp was used as a sunlight simulating light source with a light intensity of 20 mW / cm 2 , the reaction time was 2 h, and the control group was pure darkness or inactivated carbonaceous semiconductor material. The different pollutant types and concentration groups in Table 3 were transferred and cultured (dilution ratio 1:100, 200 rpm, 30℃, 12 h). Figure 6 (A) It can be seen that 0.1-1 mM sodium nitrate, 1-100 mg / L methyl green or 1-30 mg / L sulfamethoxazole have little effect on microbial activity, which is equivalent to the control group. At the same time, photocatalytic pollutant degradation experiments were carried out on each group to determine the optimal experimental conditions. Figure 6 (B) The degradation rates of living carbonaceous semiconductor materials CdS / RGO / SW and control materials CdS / RGO to 0.1, 1 or 10 mM sodium nitrate concentrations are shown. The results show that group 11 has the best degradation effect (1 mM sodium nitrate), and there is almost no degradation of dark CdS / RGO in each group, indicating that the degradation of nitrate comes from microorganisms. The photocatalytic promotion effect is obvious, that is, the degradation rate of illuminated CdS / RGO / SW is 8.6 times that of dark CdS / RGO / SW, and the illuminated CdS / RGO / SW is 4.9 times that of illuminated CdS / RGO. Figure 6(C) The degradation rate of methyl green at 1, 100 or 500 mg / L concentration by the living carbonaceous semiconductor material CdS / RGO / SW and the control material CdS / RGO is shown. The results show that group 14 has the best degradation effect (100 mg / L methyl green). Different concentrations of CdS / RGO groups were slightly degraded in the dark. It is speculated that the material has a small adsorption effect on methyl green, and the introduction of SW enhances this process. Light promotes the degradation of methyl green by CdS / RGO / SW and CdS / RGO, and the light-exposed CdS / RGO / SW is 4.9 times that of the dark CdS / RGO / SW, and the light-exposed CdS / RGO / SW is 2.6 times that of the light-exposed CdS / RGO. Figure 6 (D) shows the degradation rate of 1, 30 or 200 mg / L sulfamethoxazole by the living carbonaceous semiconductor material CdS / RGO / SW and the control material CdS / RGO. The results show that the degradation effect of groups 17 and 18 is better, but the background concentration of group 17 (30 mg / L sulfamethoxazole) is much lower than that of group 18 (200 mg / L sulfamethoxazole). Figure 6 (A) It can be seen that 200 mg / L sulfamethoxazole has a certain toxic effect on microorganisms. Taking all factors into consideration, the optimal degradation condition is 30 mg / L sulfamethoxazole. Under this condition, the concentration of illuminated CdS / RGO / SW is 2.7 times that of dark CdS / RGO / SW, and the concentration of illuminated CdS / RGO / SW is 1.8 times that of illuminated CdS / RGO. In summary, the optimal conditions for pollutant concentration are 1mM sodium nitrate, 100 mg / L methyl green, and 30 mg / L sulfamethoxazole.
[0058] Comparative Example 1: Comparison of the properties and performance of chemically synthesized CdS / RGO and biologically synthesized CdS / RGO
[0059] (1) Method for chemical synthesis of CdS / RGO: 0.514 g CdCl2·2.5H2O, 0.19 g thiourea, and 1 g polyvinyl pyrrolidone (PVP) were mixed in 50 mL ethylene glycol under stirring conditions, and then 2.5 mL GO mixed solution (150 mg GO / 15 mL ethylene glycol mixed solution) was added. After stirring, the mixture was subjected to hydrothermal reaction at 160 °C for 12 h. Subsequently, the synthesized CdS / RGO (the content and ratio of the precursor of CdS / RGO synthesized by biological method are consistent, i.e., 0.3 mM CdS and 50 mg / L GO) was obtained by washing the mixture several times.
[0060] (2) Performance index test of the CdS / RGO material synthesized by chemical method in this example: Figure 7The morphology characteristics of chemically synthesized CdS / RGO materials, its CdS particle size distribution and XRD results are shown. The results show that CdS in chemically synthesized materials is also in close contact with RGO, but its particle size is about 1037.9nm, which is much larger than the 28.14 nm of the biological method. Figure 7 (C) shows that the XRD of the chemically synthesized material corresponds to the CdS card (PDF#41-1049), which belongs to the hexagonal system; Figure 5 (B) XRD of biologically synthesized materials corresponds to CdS card (PDF#10-0454), which belongs to the cubic system. Cubic CdS is generally considered to have better photocatalytic performance due to its higher carrier migration rate and charge separation efficiency, as well as its excellent performance when forming heterojunctions. The above results show that biologically synthesized and chemically synthesized CdS / RGO are completely different materials, especially the photosensitizer CdS, which is reflected in many aspects such as morphology, particle size and crystal form.
[0061] (3) Construction of carbonaceous semiconductor material CdS / RGO / SW from different sources of CdS / RGO (biological and chemical synthesis): For the biological in situ construction of living carbonaceous semiconductor materials, the method is the same as Example 1. A chemical comparison is set up, specifically, the CdS / RGO chemically synthesized in (1) is mixed with Shewanella cultured to the late logarithmic stage according to the same concentration ratio as in Example 1 (OD600 = 0.2, CdS = 0.3 mM, RGO = 50 mg / L).
[0062] (4) Comparison of photocatalytic degradation of pollutants by living carbonaceous semiconductor material CdS / RGO / SW (CdS / RGO synthesized by biological method and chemical method): The conditions and operation are the same as those in Example 2. The construction of chemically synthesized CdS / RGO and the groups of photocatalytic degradation experiments are shown in Table 4. The pollutant concentration adopts the optimal conditions after the bacterial tolerance optimization in Example 2, that is, 1 mM sodium nitrate, 100 mg / L methyl green, and 30 mg / L sulfamethoxazole are used as the concentration conditions for the photocatalytic degradation of pollutants in Comparative Example 1.
[0063]
[0064] Figure 8 The results show that the photocatalytic degradation of various pollutants by chemical synthesis and biological in situ construction of living carbonaceous semiconductor materials CdS / RGO / SW is better than that of the chemical method in terms of photocatalytic degradation of pollutants including sodium nitrate, methyl green and sulfamethoxazole. This is due to the better performance of the photosensitizer CdS in the biologically synthesized materials and the better biological-material interface when the biological in situ construction coupling system is used.
[0065] The above are merely exemplary embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for in-situ construction of a living carbonaceous semiconductor material, characterized in that The steps include: Step 1: Cultivate the dissimilatory metal-reducing bacteria in LB medium until the late logarithmic growth stage; Step 2: The dissimilatory metal-reducing bacteria cultured to the late logarithmic growth stage in step 1 are resuspended in a culture medium containing thiosulfate for anaerobically cultured. After the reaction, heavy metal ions and carbon materials are added to the culture system so that all heavy metal ions are converted into sulfide semiconductors to obtain living carbonaceous semiconductor materials.
2. The in-situ construction method according to claim 1, characterized in that: In step 1, the dissimilatory metal-reducing bacteria stored at -80°C were streaked on a plate, cultured aerobically for 48 h, and then single colonies were selected in LB liquid culture medium, cultured aerobically for another 12 h, and then transferred to fresh LB liquid culture medium for another 12 h of aerobic culture.
3. The in-situ construction method according to claim 2, characterized in that: The dissimilatory metal-reducing bacteria is the wild-type WT strain of S. oneidensis MR-1.
4. The in-situ construction method according to claim 1, characterized in that: In step 2, the culture medium containing thiosulfate is based on LB liquid culture medium, to which thiosulfate is added, and the concentration of thiosulfate is between 0.1-5 mM.
5. The in-situ construction method according to claim 1, characterized in that: In step 2, the concentration of the heavy metal ions in the culture system is between 0.1-5 mM, and the heavy metal ions are selected from one or more of Cd(II), Hg(II), Cu(II), and Pb(II).
6. The in-situ construction method according to claim 1, characterized in that: In step 2, the concentration of the carbon material in the culture system is between 10-500 mg / L, and the carbon material includes one or more of graphene oxide and activated carbon.
7. The in-situ construction method according to claim 1, characterized in that: In step 2, the anaerobic culture time with thiosulfate is 6-12 h; the thiosulfate is sodium thiosulfate.
8. The in-situ construction method according to claim 1, characterized in that: In step 2, the culture time after the addition of heavy metals and carbon materials is 6-12 h.
9. Use of the active carbonaceous semiconductor material prepared by the preparation method according to any one of claims 1 to 8 in photocatalytic degradation of pollutants.
10. The use according to claim 9, characterized in that: The pollutants include one or more of nitrates, antibiotics, and organic dyes; The nitrate includes one or more of lithium, sodium and potassium nitrates; the antibiotic is a sulfonamide antibiotic; and the organic dye is a methyl dye.
11. The use according to claim 10, characterized in that: The living carbonaceous semiconductor material is transferred into a liquid inorganic salt medium containing pollutants and photocatalytically degraded in an argon atmosphere; The components of the liquid inorganic salt culture medium include: NaCl 0.4-0.5 g / L, (NH4)2SO4 0.2-0.3 g / L, K2HPO4·3H2O 2.5-3.5 g / L, KH2PO4 2-3 g / L, Na2HPO4·12H2O 8.5-9.5 g / L, NaH2PO4·2H2O 2-3 g / L, MgSO4·7H2O 0.02-0.03 g / L, and sodium lactate 15-25 mM.
Citation Information
Patent Citations
Method for degrading organic pollutant through nanometer material photo-reduction and assisted by electricigens
CN102936060A
Biosynthesis method of FeS-coated rGO composite material
CN111318287A
Cadmium sulfide / Shewanella oneidensis hybrid system and preparation and carbon sequestration method thereof
CN116814453A
Method for degrading plastic to produce hydrogen based on shewanella biofilm mineralized cadmium sulfide
CN117904211A